Determination of Aflatoxins in Feed by HPLC and PCR - Areej Zuhair Azeez; Mrwa Thamer Hindi; Maha Muhamed Khudiar; Adel Saadi AL Saadi; Noor Ibrahim Khadim (Journal of Food and Pharmaceutical Sciences, 2020)
The aim of this study is to identify aflatoxin secretion isolates in animal feeds by using HPLC and PCR methods . In this study we collected fourty three samples of animal feed from different sites in Iraq (maize ,soybean ,sunflower grain ,barley grain, wheat). we isolated fungi on potato dextrose agar, Aspergillus flavus fungi was isolated from this samples and identified the enzyme activities were tested for this isolate. The detection and determination for aflatoxin secretion of the isolates were done by using High Performance Liquid Chromatography (HPLC) technique. Twelve isolates shown Aflatoxin B1 secretion. Polymrease chain reaction ( PCR) technique is an alternative method to detect for Aspergillus spp. strains that secret aflatoxin by using specific primers( ITS1) endogenous gene for Aspergillus flavus and (ord , nor) genes for aflatoxin B1 secreation, the PCR technique considered to be an important role for safety and quality in industrial food and feed.